Implementasi Pembinaan Muallaf Melalui Pendidikan Islam Di Kota Samarinda - Omik Bustomi; Suprapti Suprapti; Abem Ngisti; Annisa Khairani; Nurhalimah Nurhalimah; Fadzlullah Fadzlullah; Norlita Norlita (Jurnal Tarbiyah dan Ilmu Keguruan Borneo, 2022)
Based on the phenomena that occurred at Bina Mualaf Institute in Samarinda City, there were differences in improving the practice of Islam, including at the planning, implementation, and decision-making stages of deliberation and consensus among the converts. Therefore, this study aims to describe the strategy of Bina Mualaf Institute in planning the program for converting to Islam through daily, weekly, monthly, six-monthly, annual and various kinds of skills. Reality shows that religion does not belong only to the lower class but belongs to all levels of society without using the classification system. This research is qualitative with a case study approach. The subjects selected in this study were limited to the management of Bina Mualaf Institute for converting to Islam, converts to converts, and converts to Islam with the age limit criteria being 25 years of converts. The researcher chose Bina Mualaf Institute of Samarinda City based on the researcher's initial observations that there were some converts who returned to their previous religion. To get the data as a whole, the researcher used observation, documentation and interview techniques. While the data analysis technique, the researcher uses the Miles and Huberman technique in three stages, namely data condensation, data display, and verification. The data obtained will be tested through the persistence technique of observing source triangulation and technical triangulation. The results of this study revealed that; Planning for converting converts can be traced through daily, weekly, monthly, six-monthly and yearly recitations. The implementation carried out by Bina Mualaf Institute in coaching is at three location points, namely at the secretariat of Bina Mualaf of the Islamic Center Mosque, in sub-district of Loa Janan, and Cendarawasi Samarinda City.